2020
DOI: 10.31073/mivg202001-235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on water resources and agricultural production

Abstract: The article highlights the research results on the assessment of natural moisture supply in Ukraine, the state of water resources and agricultural production in the face of modern climate change taking into account the forecast for the medium and long term prospects. It was established that the rate of air temperature growth for the period of 1975-2019 in Ukraine ranges from 0.61 to 0.82oC, while in neighboring post-Soviet countries (Russia, Moldova, Belarus) – this figure is 0.47 - 0.59oC, and in the northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
11
0
4
Order By: Relevance
“…According to the results of assessing the regional warming rates, it was found that in the south and north-east of the country in 1991-2019 the average annual air temperature turned out to be by 1.0-1.1 ºC higher than for the standard period , in the west -by 1.2-1.3 ºC, and in the north and in the central regionsby 1.4-1.5 ºC. That is, the growth rate of air temperature for 1975-2019 ranges from 0.61 to 0.82 ºC per 10 years, while in the neighboring post-Soviet countries (Russia, Moldova, Belarus) -0.47-0.59 ºC per 10 years [1], and in the northern hemisphere and Europe -0.34 and 0.47 ºC per 10 years, respectively. These data indicate that the rate of air temperature rise in Ukraine is much higher than the European and global scales.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…According to the results of assessing the regional warming rates, it was found that in the south and north-east of the country in 1991-2019 the average annual air temperature turned out to be by 1.0-1.1 ºC higher than for the standard period , in the west -by 1.2-1.3 ºC, and in the north and in the central regionsby 1.4-1.5 ºC. That is, the growth rate of air temperature for 1975-2019 ranges from 0.61 to 0.82 ºC per 10 years, while in the neighboring post-Soviet countries (Russia, Moldova, Belarus) -0.47-0.59 ºC per 10 years [1], and in the northern hemisphere and Europe -0.34 and 0.47 ºC per 10 years, respectively. These data indicate that the rate of air temperature rise in Ukraine is much higher than the European and global scales.…”
Section: Resultsmentioning
confidence: 97%
“…Usually, an increase in air temperature increases the moisture holding capacity of the atmosphere [1]. With an increase in air temperature by 1 ºC, the water-holding capacity of air increases by about 7% [1; 2], which leads to an increase in potential evaporation [1].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations